The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1590/s0074-02762001000900007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of fecal egg excretion during Schistosoma mansoni infection in an endemic area in Minas Gerais, Brazil

Abstract: There is considerable variation in the level of fecal egg excretion during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…A genetic analysis of hookworm infection in Zimbabwe (Williams-Blangero et al, 1997) estimated a heritability of 0.37 in the population indicating genetic factors to be responsible for 37% of the variation (after correcting for confounding environmental factors) seen in faecal EPG. A strong genetic effect (37–44%) was also detected in intestinal schistosomiasis caused by S. mansoni in a population in Brazil (Bethony et al, 2001; Bethony et al, 2002) and shared household environment was also shown to be important and accounted for 12–21% of the phenotypic variation seen in infection intensity. In contrast, a family based study in Kenya that investigated the aggregation of S. haematobium infection, obtained a low heritability score for the trait (King et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…A genetic analysis of hookworm infection in Zimbabwe (Williams-Blangero et al, 1997) estimated a heritability of 0.37 in the population indicating genetic factors to be responsible for 37% of the variation (after correcting for confounding environmental factors) seen in faecal EPG. A strong genetic effect (37–44%) was also detected in intestinal schistosomiasis caused by S. mansoni in a population in Brazil (Bethony et al, 2001; Bethony et al, 2002) and shared household environment was also shown to be important and accounted for 12–21% of the phenotypic variation seen in infection intensity. In contrast, a family based study in Kenya that investigated the aggregation of S. haematobium infection, obtained a low heritability score for the trait (King et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Population size and the extent of the study area prevented us from introducing adjustment for exposure based on water contact, as has been done in some previous studies. 7,13,14 Water contact in the present study area takes place in multiple dispersed surface ponds, and both snail infection levels and water use vary extensively from season to season. 3,33,34 Previous multivariate analysis of environmental predictors of infection risk in the Msambweni study area have shown the degree and duration of water contact to be much less effective predictors of infection/reinfection than age, gender, and location of residence.…”
Section: Discussionmentioning
confidence: 96%
“…Heritable risk for S. mansoni infection intensity has also been suggested by recent population-based family studies in Brazil, which have indicated that 20−44% of the variance in their infection levels appears related to heritable effects. 13,14 In addition, population-based studies of intestinal helminthic infections (Ascaris lumbricoides [roundworm], Trichuris trichiura [whipworm], and hookworm) suggest a moderate but significant heritable component to risk for these other worm infections. 13,15−17 With this in mind, we undertook the present study to estimate the influence of hereditary factors in determining risk for infection and urinary tract disease caused by the parasite S. haematobium in a high transmission area of coastal Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Unaccounted household-level variability may alternatively be explained by intrinsic host-related factors such as genetics [51],[52], nutrition [53], immune response [54],[55] or concomitant infection with other parasites [56]. Despite an increasing number of studies suggesting a genetic component to variation in intensity of helminth infection, the relative importance of host genetics and exposure remain unclear and vary considerably between the settings studied (reviewed in [57] and [58]).…”
Section: Discussionmentioning
confidence: 99%